Development Potential of AR Anatomy as an Interactive Learning Medium for Elementary Science Education - Muhammad Fiqri Zulfikar; Nabila Ismawarni.Ka; Dyah Ayu Kusumaningtyas; Syahrul Ramadhon; Irba Ilzami Al Haq; Muhammad Zainudin Al Amin (S1 Teknologi Informasi, Universitas Muhammadiyah Semarang, 2025)
In the era of the Industrial Revolution 4.0 and Society 5.0, education is expected to deliver adaptive, interactive, and contextual learning experiences. One of the main challenges in elementary science education lies in teaching abstract concepts such as human anatomy, where traditional textbooks and two-dimensional images often fail to support deep understanding. Augmented Reality (AR) offers a promising alternative by enabling the real-time visualization of three-dimensional (3D) models through mobile devices. This study explores the development and potential of “AR Anatomy,” a camera-based AR application designed to provide interactive visualizations of human organs for elementary students. Using a qualitative literature review of recent studies published after 2022, the analysis indicates that AR Anatomy can enhance student motivation, active engagement, and spatial understanding, while offering a cost-effective alternative to physical anatomical models. Nevertheless, limitations remain, including restricted organ coverage, lack of integrated evaluation features, and limited alignment with the national curriculum. In conclusion, AR Anatomy represents a promising step toward technology-enhanced science education at the elementary level, with further refinement needed to improve content coverage and classroom implementation.